Ankle bracing effects on knee and hip mechanics during landing on inclined surfaces. Issue 1 (1st January 2016) - Theodorakos, Ilias; Rueterbories, Jan; Lund, Morten E.; Andersen, Michael S.; de Zee, Mark; Kersting, Uwe G.
Abstract: Knee and hip alignment and knee moments during landing are considered risk factors for knee injuries while ankle bracing has been demonstrated to alter landing kinematics and kinetics at these joints. The aim of this study was to investigate whether a semi-rigid ankle brace has an effect on knee and hip kinematics and kinetics during landing on uneven surfaces. Seventeen recreational athletes performed a landing task on a randomly inclined platform with and without an ankle brace. Three different surface alignments were generated: everted, neutral, and inverted. Ground reaction forces (GRF), kinematics, and brace reaction forces were measured. Two independent variables were tested: the brace factor (braced and non-braced) and the inclination factor (everted, neutral, and inverted). Seven separate 2 × 3 repeated measures MANOVAs were employed to compare GRF, knee, and hip initial angles and range of motion (ROM), knee, and hip forces and moments. Participants landed with a more flexed knee and hip during the brace condition, followed by a knee ROM reduction. No differences were observed for the kinetic variables. Landing on the inverted surface resulted in increased peak magnitudes of the vertical and the mediolateral GRF compared to landing on the neutral surface. Landing on the everted surface caused higher knee and hip abduction moments during early contact. Results confirm that ankle bracing may affect the kinematics of the whole lower extremity with no effect on knee or hip loading. Landing on uneven surfaces may increase injury risk, but no adverse effects were shown for wearing the brace.